Analysis of clinical factors as possible predictors of response to omalizumab and relapse after treatment discontinuation in chronic spontaneous urticaria. Issue 2 (16th December 2021) - Foti, Caterina; Romita, Paolo; Ambrogio, Francesca; Fanelli, Margherita; Panebianco, Rosanna; Vena, Gino Antonio; Cassano, Nicoletta; Ragusa, Mariagrazia; Giuffrida, Roberta; Papaianni, Valeria; Borgia, Francesco; Cannavò, Serafinella Patrizia; et al.
Abstract: Omalizumab is a monoclonal anti‐IgE antibody which is effective in chronic spontaneous urticaria (CSU), although clinical response appears to be variable in the real‐life setting. The aim of this study was to evaluate whether the response of CSU to omalizumab and disease relapse are associated with individual and/or clinical characteristics of patients. We retrospectively evaluated the clinical records of 124 patients treated with omalizumab for moderate to severe CSU refractory to antihistamines. Disease activity was assessed using the urticaria activity score over the last 7 days (UAS7). After 24 weeks of treatment, 91% of patients showed complete remission (UAS7 = 0) or good control (UAS7 < 7) of CSU. Omalizumab was re‐administered in 45 patients because of recurrence of moderate to severe symptoms at week 8 after treatment discontinuation or later, and clinical results achieved with retreatment were similar to those observed in the first course. Among the parameters included in our analysis (age and sex of patients, documented history of atopy or autoimmune thyroid disease, CSU duration and baseline severity, concurrent angioedema, and association with chronic inducible urticaria), none was associated with response to omalizumab in our study population. Similarly, these parameters did not significantly differ between patients who experienced CSU relapse and those without relapse. Predictors of response to omalizumab treatment in CSU patients are still unclear, and further studies are needed to evaluate the presence of baseline factors that can influence treatment outcome.